Size-Fractionated PM10 and Bioaerosol Indicator Development by Different Methods in Composting Plants for Risk Assessment - Pascale, Erica; Franchitti, Elena; Zanchi, Noemi; Anedda, Elisa; Bonetta, Sara; Traversi, Deborah (Frontiers in Environmental Science, 2022)
Rapid population growth and urbanization have led to increased waste generation rates. Avoiding, reducing and reusing waste is imperative in the international approach to avoid impacting disposals. Composting plants are crucial for better organic waste management, although one of their environmental impacts is bioaerosol production, which can lead to adverse health effects. This work analyzed bioaerosol contamination in composting plants through multiple analytic methods, including culture-based techniques and qPCR, subfractionated PM10, and PM4.5 sampling. The aim was to identify indicators useful for assessing the human health risk associated with bioaerosol exposure during organic waste treatment. Two composting plants and four different areas (reception/selection, methanization, composting and refinement) were selected for sampling. The analysis revealed high contamination levels and large microbial heterogeneity both for PM (until to 3 times above the guideline value) and bioaerosol samples (until to 3 magnitude orders above the proposed reference value). Bacillus spp., Saccharopolyspora, and Thermomyces always showed detectable but highly variable concentrations (ranging from 2.12 to 4.86, from 3.65 to 7.30 and from 3.45 to 6.94 Log gene copies/m3 respectively). They correlated positively and significantly with other measured microbial parameters, suggesting their potential use as indicators of biological contamination in composting plants. Moreover, the integration of nonculture-based methods can increase the monitoring sensitivity and improve the bioaerosol risk assessment. The reduction of bioaerosol exposure levels in composting plants remains a primary goal but it requires in-depth characterization of the complex bioaerosol composition, its airborne dispersion, and its association with specific adverse health outcomes.